The ACE gene and endurance performance during the South African Ironman Triathlons - Collins, M.; Xenophontos, S. L.; Cariolou, M. A.; Mokone, G. G.; Hudson, D. E.; Anastasiades, L.; Noakes, T. D. (Medicine & Science in Sports & Exercise, 2004)
PURPOSE: Several studies have suggested that the insertion (I) variant rather than the deletion (D) variant of the human angiotensin-converting enzyme (ACE) gene is associated with elite endurance performance. The aim of this study was to determine whether the ID polymorphism is associated with the performance of the fastest finishers of the South African Ironman Triathlons. METHODS: A total of 447 Caucasian male triathletes of a variety of nationalities and athletic ability who completed either the 2000 or 2001 South African Ironman Triathlons and 199 Caucasian male control subjects were genotyped for the ACE ID polymorphism. RESULTS: There was a significantly higher frequency of the I allele in the fastest 100 South African-born finishers (103 I, 51.5% and 97 D, 48.5%) compared with the 166 South African-born control subjects (140 I, 42.2% and 192 D, 57.8%) (P = 0.036). There was also a significant linear trend for the allele distribution among the fastest 100 finishers (I allele = 51.5%), slowest 100 finishers (I allele = 47.5%), and control (I allele = 42.2%) South African-born subjects (P = 0.033). There was, however, no significant difference in the ACE genotype or allele frequencies when athletes born outside South Africa were analyzed. CONCLUSION: To our knowledge this is the first study that has examined the effect of an athlete's ACE genotype on their actual performance during an ultra-endurance race. The I allele of the ACE gene was associated with the endurance performance of the fastest 100 South African-born finishers in these triathlons.